Analisis Strategi Pemasaran Pada Lembaga Kursus dan Bimbingan Belajar Education Zone - Shinta Abdul Rahman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Marketing activities determine the Education Zone Course and Tutoring Institute (E-Zone LKBB) in selling products as the spearhead set by the E-Zone management LKBB and its marketing strategy. In determining the marketing strategy, environmental analysis is critical because it includes analyzing the internal and external environment. The research problem is about the service marketing strategy in the E-Zone LKBB. Therefore the research questions in this research are: 1) What are the strengths and weaknesses in improving LKBB E-Zona services. 2) What are the opportunities and threats in increasing the marketing strategy of LKBB E-Zone services? 3) What are the formulations of marketing strategies in improving marketing LKBB E-Zone services? This study aims to identify the strengths and weaknesses in the LKBB E-Zone as well as the opportunities and threats of the E-Zone LKBB and formulate a marketing strategy for LKBB E-Zone. The unit of analysis in this research is the Education Zone Course and Tutoring Institution. The observation unit is the marketing and sales management and the students who have studied at LKBB E-Zone for approximately six months. The data analysis method used in this study is the SWOT analysis (Strength, Weakness, Opportunity, Threat), which is an analysis that aims to analyze the strengths and weaknesses as well as opportunities and threats. The result shows that the E-Zone LKBB is in the Fast Growth Strategy quadrant position, between Strength (Strength) and opportunity (Opportunity) in the SWOT diagram. LKBB E-Zone has strengths and opportunities that are greater than weaknesses and threats. So that LKBB E-Zone can take full advantage of all the potential strengths and opportunities by using elements of marketing strategies, namely: market segmentation, target market determination, product placement, timing, marketing mix, and its essential 7 P elements, namely: Promotion, Product, Price, Place, People, Physical Evidence, and Process